2003
DOI: 10.3102/0013189x032005006
|View full text |Cite
|
Sign up to set email alerts
|

“Every Shut Eye Ain’t Sleep”: Studying How People Live Culturally

Abstract: We call for the integration of cultural socialization and identity processes in learning as a goal of educational research. Our aim is to improve educational outcomes for racial and ethnic minority youth and for youth facing persistent intergenerational poverty. This requires that educational researchers understand the cultural niches in which young people develop. We illustrate this claim through the lenses of the Cultural Modeling Framework and the Phenomenological Variant of Ecological Systems Theory, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 17 publications
0
101
0
Order By: Relevance
“…Youth from less privileged backgrounds often have resources of resilience and persistence that help them confront and thrive in new situations (Lee, Spencer, & Harpalani, 2003;Yosso, 2005). At the same time, they may have less exposure to wide ranges of possible futures than their more privileged peers.…”
Section: Insights About Engaging Diverse And/or Fearful Learners In Ementioning
confidence: 99%
“…Youth from less privileged backgrounds often have resources of resilience and persistence that help them confront and thrive in new situations (Lee, Spencer, & Harpalani, 2003;Yosso, 2005). At the same time, they may have less exposure to wide ranges of possible futures than their more privileged peers.…”
Section: Insights About Engaging Diverse And/or Fearful Learners In Ementioning
confidence: 99%
“…Instead, differences in ability are attributed to learners' participation in specific cultural-historically situated activity systems rather than being blamed on disadvantage and deficits (Gutiérrez & Rogoff, 2003) or narrow conceptions of competence (Gipps, 1999). For example, there has been ongoing research with Bakhtinian forms of discursive practices, or what is called "third spaces" (e.g., Gutiérrez, Baquedano-López, Alvarez & Chiu, 1999;Gutiérrez, Rymes, & Larsen, 1995), while others who work with African American communities have capitalized on the normally undervalued funds of knowledge that these learners embody (e.g., C. D. Lee, 2001; C. D. Lee & Majors, 2003; C. D. Lee, Spencer, & Harpalani, 2003;Majors, 2003). Alternatively, research in technology-intensive learning environments allows students to interact in model activity systems such as Michael Cole's Fifth Dimension (Cole, 1995(Cole, , 1996Nicolopoulou & Cole, 1993), Kris Gutiérrez's Las Redes (Gutiérrez, Baquedano-López, & Tejeda, 1999), and Sasha Barab's Quest Atlantic program (Barab, Hay, Barnett, & Squire, 2001).…”
Section: Collaboration: Enacting Learning and Developmentmentioning
confidence: 99%
“…Previous studies have shown that hybrid learning environments allow students to take alternative paths to understanding and thus favor the engagement of minority students in meaningful and productive ways in school subjects, increasing minority students' opportunities for accessing the knowledge of the traditional school domains (Lee, Spencer, & Harpalani, 2003). The results of the research reported here show that in interactive groups hybrid avenues of participation are encouraged, among other reasons, because the contributions of all participants are equally valued on the basis of the arguments provided (egalitarian dialogue).…”
Section: Discussionmentioning
confidence: 99%